2018
DOI: 10.3390/en11040784
|View full text |Cite
|
Sign up to set email alerts
|

Linear and Nonlinear Causality between Energy Consumption and Economic Growth: The Case of Mexico 1965–2014

Abstract: This paper analyzes the causal link between aggregated and disaggregated levels of energy consumption and economic growth in Mexico between 1965 and 2014, with the presence of structural breaks stemming from the series. To that end, unit root with structural breaks, cointegration, and linear and nonlinear causality tests are employed. The results show that there is a long-run relationship between production, capital, labor, and energy, and linear causal links from total and disaggregated energy consumption to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 45 publications
0
17
0
5
Order By: Relevance
“…Further research in this field would be of great help, with different methods such as Residual Augmented Least Squares Lagrange Multiplier (RALS-LM) suggested by [72] (see, Ref. [38] for example) as well as considering the non-linear aspects by investigating the cointegrating relationship with asymmetric techniques such as the non-linear ARDL in [73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research in this field would be of great help, with different methods such as Residual Augmented Least Squares Lagrange Multiplier (RALS-LM) suggested by [72] (see, Ref. [38] for example) as well as considering the non-linear aspects by investigating the cointegrating relationship with asymmetric techniques such as the non-linear ARDL in [73].…”
Section: Discussionmentioning
confidence: 99%
“…A structural break in the time series occurs due to some unique economic events [37]. From energy-financegrowth aspects, such events include the changes in economic conditions, changes in energy policy, and fluctuations in the price of energy [38], legislative or technical changes [39]; consequently, these can have a permanent effect on the pattern of the time series [40]. Hence, it is critical to identify structural breaks in the data to avoid model misspecification and coefficient bias and to ensure that tests for the non-stationarity of the data give the correct result [41]; ignoring such break when it is present can result in misinterpretation by reducing the ability to reject a false unit root null hypothesis [37].…”
Section: Introductionmentioning
confidence: 99%
“…The Brent blend crude oil price has been widely used in previous studies [7,22,23], and the GDP used in this study was GDP per capita (in current U.S. dollars). These proxies have been widely used in previous studies [24][25][26]. The descriptive values for skewness and kurtosis in Table 1 indicated that all of the parameters were not normal.…”
Section: Data and Variablesmentioning
confidence: 99%
“…To a certain extent, this can reduce the waste of energy, so that the consumption of energy can be reduced relatively. Many studies showed that there is a close relationship between economic growth and energy consumption [43,44]. For example, Apergis' results revealed the presence of unidirectional causality from energy consumption to economic growth in the short-term, and bidirectional causality between energy consumption and economic growth in the long-term [43].…”
Section: Economic Level (Pgrp)mentioning
confidence: 99%